Why is There Not More Demand for Redistribution? Cross-National Evidence for the Role of Social Justice Beliefs. (14th February 2018) - Lierse, Hanna
Abstract: Income inequality has risen throughout advanced rich democracies. Why does the public not demand more redistribution? This article builds on the literature of social justice norms, which shows that besides individual financial motives also socially engrained beliefs about poverty influence opinions about redistribution. Based on a multilevel analysis of public opinion data from 33 countries, the article shows that lower levels of support for redistribution are not driven by political polarization between the rich and the poor, but it is rooted in deeply seated societal norms among all income groups. The unfortunate implication of this finding is that simple, short-run policy is unlikely, which could mitigate existing economic imbalances.